2015
DOI: 10.1152/ajpendo.00518.2014
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear retinoid-related orphan receptor-α regulates adipose tissue glyceroneogenesis in addition to hepatic gluconeogenesis

Abstract: Circadian rhythms have an essential role in feeding behavior and metabolism. ROR␣ is a nuclear receptor involved in the interface of the circadian system and metabolism. The adipocyte glyceroneogenesis pathway derives free fatty acids (FFA) liberated by lipolysis to reesterification into triglycerides, thus regulating FFA homeostasis and fat mass. Glyceroneogenesis shares with hepatic gluconeogenesis the key enzyme phosphoenolpyruvate carboxykinase c (PEPCKc), whose gene is a ROR␣ target in the liver. ROR␣-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 51 publications
(69 reference statements)
0
24
0
Order By: Relevance
“…Interestingly, although RORa is a transactivator of gene expression, our data suggested that it inhibits the thermogenic program of WAT. Although more work is required to tease out the exact molecular processes, this study demonstrates the pivotal role of RORa in energy homeostasis and makes it an interesting therapeutic target for treatments focusing on artificially increasing energy expenditure as a way of handling obesity, all the more so since it has been shown that RORa inverse agonists are also able to decrease hepatic neoglucogenesis (Kumar et al 2011;Kadiri et al 2015…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, although RORa is a transactivator of gene expression, our data suggested that it inhibits the thermogenic program of WAT. Although more work is required to tease out the exact molecular processes, this study demonstrates the pivotal role of RORa in energy homeostasis and makes it an interesting therapeutic target for treatments focusing on artificially increasing energy expenditure as a way of handling obesity, all the more so since it has been shown that RORa inverse agonists are also able to decrease hepatic neoglucogenesis (Kumar et al 2011;Kadiri et al 2015…”
Section: Discussionmentioning
confidence: 87%
“…The ROR family, which includes RORα, β, and γ, activates transcription at ROR response elements through recruitment of co-activators such as PGC-1α 212 and steroid receptor co-activator 2 (SRC2) 213 . Loss of RORα leads to fasting hypoglycemia and decreased expression of gluconeogenic genes in the liver 214 .…”
Section: Strategies To Modulate Liver Glucose and Glycogen Metabolismmentioning
confidence: 99%
“…Only RORα and RORγ are highly expressed in the liver, while RORβ is expressed mainly in the central nervous system (Forman et al 1994;Andre et al 1998;Takeda et al 2012). Studies of total body knockout mice reported that both RORα-and RORγ-deficient mice exhibited improved insulin sensitivity and glucose tolerance with decreased hepatic gluconeogenesis (Takeda et al 2014a;Kadiri et al 2015). RORα-deficient mice, which suffer from severe cerebellar defects and display a staggerer phenotype (Sidman et al 1962;Dussault et al 1998;Steinmayr et al 1998), also exhibited lower total body fat and were resistant to age-induced white adipose tissue (WAT) and brown adipose tissue (BAT) hypertrophy (Kang et al 2011).…”
mentioning
confidence: 99%